Unwanted pregnancies among teenagers in Malaysia: a growing concern / Siti Hajar Md. Jani and Dr. Jamali Wagiman - Md.Jani, Siti Hajar; Wagiman, Jamali (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
Unwanted pregnancies among teenagers have been a global public health issue for many years. In Malaysia, this problem has gained significant attention in recent times. With its diverse population and rapidly changing social landscape, the country is facing an increasing rate of unwanted pregnancies among adolescents. This article explores the factors contributing to this issue and the measures being taken to address it. Teenage pregnancies in Malaysia have increased at an alarming rate in recent years. According to data from the Ministry of Health Malaysia, the rate of teenage pregnancies increased by 42% between 2010 and 2020. In 2010, there were approximately 15,000 reported cases of teenage pregnancies, while in 2020, this number rose to over 21,000. These statistics are alarming and demand immediate attention from policymakers, healthcare professionals, and communities.